Impact of Performance Appraisal and Working Environment on the Job Satisfaction and Attrition Problem in the Indian IT Industry. Issue 1 (June 2014) - Agarwal, Richa N.; Mehta, Anil
This new millennium is witnessing intense competition which is profoundly impacting the business environment. The emerging economy, in which services, communications and information technologies play a significant role has created new avenues for the skilled workers. Liberalization across border has also taken place moving towards globalization. Under such circumstances talent retention has become a big problem for the business and organizations especially in IT Industry. Researchers have done intensive and extensive research covering all the three tiers companies of Information Industry in and around Delhi NCR, Bengaluru and Pune. Researchers have tried to find out whether performance appraisal and working environment has a relation with job satisfaction and whether these variables have any role when employees decide to leave an organization in the IT industry. Researchers also tried to explore and relate other internal and external factor which might be the reasons for high attrition in the IT sector.